English Homonyms in Fashion Articles: A Meaning Component Analysis in Vogue Magazine - Nazwa Putri Ramadhanty; Ruminda; Assiddiqi , Hasbi (Institut Agama Islam Negeri Palopo, 2025)
This study aims to analyze Homonyms in fashion terms from Vogue Magazines. The research uses a qualitative descriptive method to describe the data and each word's components. Language as an arbiter can have double meanings and is known as a Homonym in the study of semantics. Semantics is the study of the meaning of words. In this research, writers used Vogue magazines as the object; the research used homonyms theory by Saeed to find what types of homonyms in the articles of Vogue Magazines and the meaning components contained in fashion terms. Homonyms are divided into two types: Homographs and Homophones. The data were collected by reading several magazine articles and choosing words unfamiliar with fashion terms. Each of the words in fashion terms has a different component. The results show that homographs are the most used words in fashion terms.